THE INFLUENCE OF SERVICE QUALITY, PRICE AND PRODUCT QUALITY ON CUSTOMER SATISFACTION AT THE SOUL PROMISE COFFEE SHOP IN THE NORTH JAKARTA AREA - Jodi Setyawan; Siti Nurafiah (International Journal Management and Economic, 2023)
The purpose of this study is to determine and analyze the influence of quality Service, price and product quality to customer satisfaction coffee shop Soul Promise. Methods of analysis in this study using qualitative primary data, the test phase conducted is a test of validity, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression, coefficient of determination, F-test and t-test. Data used in this study using questionnaire instruments, and valid data collected by 100 respondents. Methods regular sampling. Testing tools called are SPSS v26. The results showed that partially variable quality service, price and product quality have a significant effect on satisfaction customers of Janji Jiwa coffee shop in North Jakarta area. Simultaneously variable service quality, price and product quality together affect significant to customer satisfaction Janji Jiwa coffee shop in Jakarta North.